2022
DOI: 10.1038/s41584-022-00749-9
|View full text |Cite
|
Sign up to set email alerts
|

Synovial inflammation in osteoarthritis progression

Abstract: Osteoarthritis (OA) is a progressive degenerative disease resulting in joint deterioration. Synovial inflammation is present in the OA joint and has been associated with radiographic and pain progression. Several OA risk factors, including ageing, obesity, trauma and mechanical loading, play a role in OA pathogenesis, likely by modifying synovial biology. In addition, other factors, such as mitochondrial dysfunction, damage-associated molecular patterns, cytokines, metabolites and crystals in the synovium, act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
229
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 439 publications
(291 citation statements)
references
References 259 publications
6
229
0
Order By: Relevance
“…Profound injury-induced changes in both proportion and abundance of subsets occurred by 7d ACLR; all clusters expanded numerically post-injury but the most robust increases were evident in subsets absent from healthy synovium – the αSMA+ and Sox9+ clusters (Figure 2E-G). Notably, the abundance of all subsets diminished by 28d ACLR, apart from Prg4 hi lining SFs, consistent with persistent lining hyperplasia observed in human PTOA(28, 29). Having defined distinct SF clusters and their temporal abundance, we assessed whether their unique transcriptomic profiles underpinned distinct functional roles.…”
Section: Resultssupporting
confidence: 79%
“…Profound injury-induced changes in both proportion and abundance of subsets occurred by 7d ACLR; all clusters expanded numerically post-injury but the most robust increases were evident in subsets absent from healthy synovium – the αSMA+ and Sox9+ clusters (Figure 2E-G). Notably, the abundance of all subsets diminished by 28d ACLR, apart from Prg4 hi lining SFs, consistent with persistent lining hyperplasia observed in human PTOA(28, 29). Having defined distinct SF clusters and their temporal abundance, we assessed whether their unique transcriptomic profiles underpinned distinct functional roles.…”
Section: Resultssupporting
confidence: 79%
“…The inflammatory microenvironment of the OA joint is found to be orchestrated by macrophages, neutrophils, and multiple inflammatory cytokines. Previous studies have demonstrated the importance of macrophages and neutrophils in driving inflammatory and destructive responses in OA ( 32 , 33 ). These results indicated there is a triggering low-grade inflammatory cycle that leads to the infiltration of macrophages and neutrophils and further induce structural changes in the synovial tissues of OA rats.…”
Section: Discussionmentioning
confidence: 98%
“…Proinflammatory cytokines have an important role in OA joint destruction [ 8 , 37 ], promoting damage in joint extracellular matrices and stimulating the progression of OA [ 9 , 10 ]. High IL-1β and TNF-α levels upregulate proteolytic enzymes, such as MMPs and ADAMTS family, which degrade the extracellular matrix [ 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%